Reducing the environmental load of triacetyl cellulose film production using wood pulp - Koo, Chong Min; Hyun, Su Jeong; Lee, Jonghwi; Hong, Soon Man (WILEY, 2015)
Triacetyl cellulose (TAC) films, which are currently produced mainly from cotton linter, are widely used for liquid crystalline display (LCD) applications. However, cotton linter is an expensive source of cellulose and the environmental load related with cotton cultivation is notoriously heavy. Herein, the replacement of cotton linter by wood pulp was systematically investigated to explore the possibility of TAC production using a less expensive source. The mechanical and thermal properties of TAC films made from wood (wTAC) were outstanding compared to those of TAC films made from cotton (cTAC). The optical transparency of wTAC was also excellent. While Tinuvin (a UV stabilizer) produced more isotropic structures in cTAC films, it produced more anisotropic structures in wTAC films. Overall, the optical films of wTAC showed good performance for LCD applications, comparable to that of cTAC. These results could be used to develop more environmentally friendly production methods for optical TAC films. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42146.
Keywords: BIREFRINGENCE; DISSOLUTION; FIBERS; COTTON; BATCH